FACTORS AFFECTING THE ADOPTION OF ELECTRONIC BUSINESS FOR EFFICIENCY IMPROVEMENT OF SMALL AND MEDIUM ENTERPRISES IN THE KANCHANABURI SPECIAL ECONOMIC ZONE - Chooyuksakul, Tanapol; Rattanapongpinyo, Taninrat (Pathumthani University Academic Journal, 2023)
The objective of this study is to examine: 1) the degree of organizational culture, competitive environment, and adoption of electronic business among medium and small enterprises, and their impact on efficiency development, 2) the interplay between organizational culture, competitive environment, and adoption of electronic business, and 3) the effect of electronic business adoption on efficiency development among medium and small enterprises within the Kanchanaburi special economic zone. The research participants consist of entrepreneurs, managers, and designated staff who can provide relevant information. The study used a questionnaire as a tool to collect data from 100 companies and analyzed the data by using structural equation modeling. The study found that 1) the level of organizational culture, the competitive environment, the use of electronic business, and the development of the performance of medium and small enterprises, in general, were at a high level, 2) organizational culture and the competitive environment has a positive impact on the use of electronic business in terms of strategy, flexibility and ability to respond quickly create competitive advantages. and 3) the use of electronic business has a positive impact on the efficiency development of medium and small enterprises in terms of efficiency and sales growth.